2 - Competencies and Proficiencies in Special Education: The Case of Ethiopian Universities - Woldehana, Workneh E.; Teferra, Damtew (Journal of Higher Education in Africa, 2022)
This study explores and analyses the competencies and proficiencies of final- year university students studying special education in two public higher education institutions in Ethiopia. A total of fifty-five final-year students were purposefully sampled with the results that these students severely lacked the requisite competencies and proficiencies in areas and skills that are crucial for personal and professional advancement in higher education. The study also observes that the training of university students does not sufficiently incorporate practical experiences and effective exposure to the tools and methods that schools employ to provide robust special education services. The study, based on the analysis of knowledge of the Individual Education Plan, concludes that final-year students involved in this study lack the requisite competencies, experiences and proficiencies which are key skills necessary for special education teachers.